2D cellular automaton – finite element simulation of grain structure and macrosegregation during solidification of Al-4wt% Cu Alloy. (1st November 2016) - Liu, Dong Rong; Yang, Yang; Sun, Qing Ya; Guo, Er Jun
Abstract: The evolution of grain structure and formation of macrosegregation during solidification of Al-4wt% Cu alloy are simulated. A two-dimensional (2D) cellular automaton (CA)–finite element (FE) model is presented. The influences of the macroscopic transport of liquid momentum, heat and solute mass on the development of grain structure are accounted for. Experiments are performed in a sand mould with graphite chill placed on one side of the cavity. Comparisons of CAFE simulation with the measured concentration of copper and with the experimental grain structure are performed. A reasonable agreement is achieved concerning columnar-to-equiaxed transition from different directions and final concentration distribution. Simulations show that only with convection in the liquid can the experimental results be reproduced. Fluid flows affect the formation of grain structure by modifying the distribution manner and degree of constitutional undercooling in the bulk melt. Solute suppressed nucleation (SSN) effect is promoted by convection.